Wilno mityczne we współczesnej prozie litewskiej - Peluritytė-Tikuišienė, Audinga (Studia Rossica Posnaniensia, 2024)
The myth of the founding of the city of Vilnius became particularly important in Lithuanian art in the decade of the restoration of independence. After a long period of occupation, the capital of Lithuania became not only a catalyst for new formulations of national and civic identity, but also a symbol of freedom. The landscape and architecture of the Old Town of Vilnius embody the archaic Baltic imagination, which is not upstaged but, on the contrary, complemented by the Christian world of Vilnius. The restoration of independence activated the archaic Baltic imagination in Lithuanian art and literature as this kind of imagination had nurtured Lithuanians’ national self-awareness over centuries. This article focuses on two modern Lithuanian prose writers, Antanas Ramonas (1947–1993) and Ričardas Gavelis (1950–2002), whose works evoke the two most striking and different images of the same mythical Vilnius – divine and demonic, hopeful and hopeless. These two opposing images of mythical Vilnius reveal two different viewpoints on the world, on history and on the human being in modern Lithuanian literature.